Hesperidin potentiates the chemosensitivity of HT-29 colon cancer cells to 5‐fluorouracil (Annals of Medical Research, 2023)
Aim:  Hesperidin is an important flavonoid compound of citrus fruits. It has the potential to be evaluated as a cytotoxic agent against a variety of malignant human cancer cells, especially in colon, pancreatic, breast, and other cancer types. The practical application of combination therapies is commonly used to eliminate or reduce drug resistance.Materials and Methods: In this study, hesperidin (0.001-300µM) and 5-fluorouracil (5-FU) (1-300 µM), a cytotoxic chemotherapy drug used for treating cancer, were applied both individually and in combination (100 µM) on the HT-29 cells (human colon cancer cell line). The effects of these compounds on HT-29 cell viability were revealed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide method, and the genotoxic effects on HT-29 cells were revealed using single-cell gel electrophoresis analysis.Results: The data obtained showed that the combination of 5-FU and hesperidin importantly decreased HT-29 cell viability compared to the group treated with 5-FU alone. These findings indicate that the combined application of these compounds is more effective than the individual administration of 5-FU or hesperidin alone.Conclusion: The research suggests that hesperidin might possess the ability to counter drug resistance in cancer cells, offering promising prospects when used alongside current anti-cancer medications. Nevertheless, to validate these findings, more extensive research and clinical trials are imperative.
Keywords: Cancer; Hesperidin; 5-fluorouracil; Cell viability; DNA damage